Serum levels of leptin and homocysteine in women with polycystic ovary syndrome and its relationship to endocrine, clinical and metabolic parameters - Atamer, A.; Demir, B.; Bayhan, G.; Atamer, Y.; Ilhan, N.; Akkus, Z. (Sage Publications Ltd, 2008)
We examined the relationship between endocrine, clinical and metabolic parameters in 35 women (mean age 27.3 years) with polycystic ovary syndrome (PCOS) and 30 age- and body mass index-matched normal ovulatory women. In PCOS women, serum leptin, homocysteine, insulin, insulin-like growth factor-1, insulin-like growth factor binding protein-3 levels and the insulin resistance index (HOMA-IR) were significantly higher, while sex hormone-binding globulin and high-density lipoprotein cholesterol levels were lower compared with healthy women. Serum luteinizing hormone (LH), estradiol (E-2), androstenedione, testosterone and dehydroepiandrosterone sulphate levels were found to be significantly higher in PCOS women compared with healthy women. The levels of E-2, LH and testosterone were positively correlated with leptin levels in PCOS women. Similarly, androstenedione levels and HOMA-IR were positively correlated with homocysteine levels and insulin levels were positively correlated with LH. We conclude that increased homocysteine levels, hyperandrogenaemia, insulin resistance and impaired lipid metabolism contribute to the risk of premature atherosclerosis in PCOS women.
7th International Congress on Coronary Artery Disease -- OCT 07-10, 2007 -- Venice, ITALY
Keywords: polycystic ovary-syndrome; insulin resistance; insulin-like growth factors; sex steroids; lipid metabolites; leptin; homocysteine